2007
DOI: 10.1016/j.scitotenv.2006.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in mRNA encoding for cell stress markers in the oyster Crassostrea gigas exposed to radioactive discharges in their natural environment

Abstract: The North Cotentin area (Normandy, France) hosts several nuclear facilities among which the AREVA reprocessing plant of La Hague is responsible for controlled discharges of liquid radioactive wastes into the marine environment. The resulting increase in radioactivity is very small compared to natural radioactivity. However, concerns about environment protection prompted the scientific community to focus on the effects of the chronic exposure to low concentrations of radionuclides in non-human biota. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 65 publications
5
31
1
8
Order By: Relevance
“…In September, mRNA levels returned to control values 48 h after stress, while in March, mRNA levels were still elevated 48 h after the heat shock. In the environment, because of natural seasonal variations, higher levels of mRNA encoding the studied genes were observed in oysters collected in March-April, compared to September (Farcy et al 2007). Higher HSP70 protein concentrations were also observed in horse mussels during winter compared to summer (Lesser and Kruse 2004).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In September, mRNA levels returned to control values 48 h after stress, while in March, mRNA levels were still elevated 48 h after the heat shock. In the environment, because of natural seasonal variations, higher levels of mRNA encoding the studied genes were observed in oysters collected in March-April, compared to September (Farcy et al 2007). Higher HSP70 protein concentrations were also observed in horse mussels during winter compared to summer (Lesser and Kruse 2004).…”
Section: Discussionmentioning
confidence: 95%
“…Firstly, the levels observed in laboratory control conditions were similar to those observed at the oyster farm, indicating that acclimation of the animals did not induce any additional stress due to handling in the laboratory. Secondly, the ranges of variation in field data, which were documented in greater detail in our previous study regarding seasonal expression patterns (Farcy et al 2007), provided a valuable basis for assessing the significance of observed changes in response to experimental exposure to stress. In the present work, heat stress values were clearly outside the ranges of control environmental and laboratory values.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations